2010
DOI: 10.1056/nejmoa1003955
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Care for Patients with Depression and Chronic Illnesses

Abstract: BACKGROUND Patients with depression and poorly controlled diabetes, coronary heart disease, or both have an increased risk of adverse outcomes and high health care costs. We conducted a study to determine whether coordinated care management of multiple conditions improves disease control in these patients. METHODS We conducted a single-blind, randomized, controlled trial in 14 primary care clinics in an integrated health care system in Washington State, involving 214 participants with poorly controlled diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
1,255
2
32

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,474 publications
(1,321 citation statements)
references
References 30 publications
32
1,255
2
32
Order By: Relevance
“…Research has shown that adherence to antidepressant medications is improved when treatment is provided in the context of a team-based collaborative care model. 32,33 Our findings are consistent with research demonstrating that models of care that are effective in improving antidepressant adherence provide opportunities for an enhanced relationship between a patient and his/her primary care team through frequent contacts, outreach, and support by care managers, as well as psychoeducation and care coordination. An extension of the chronic care model, the 'health literate care model', applies a 'universal precautions' framework in advocating for the institutionalization of practices at both the level of individual providers and the healthcare system, many of which are intended to promote trust and foster improved patient-provider relationships.…”
Section: Discussionsupporting
confidence: 86%
“…Research has shown that adherence to antidepressant medications is improved when treatment is provided in the context of a team-based collaborative care model. 32,33 Our findings are consistent with research demonstrating that models of care that are effective in improving antidepressant adherence provide opportunities for an enhanced relationship between a patient and his/her primary care team through frequent contacts, outreach, and support by care managers, as well as psychoeducation and care coordination. An extension of the chronic care model, the 'health literate care model', applies a 'universal precautions' framework in advocating for the institutionalization of practices at both the level of individual providers and the healthcare system, many of which are intended to promote trust and foster improved patient-provider relationships.…”
Section: Discussionsupporting
confidence: 86%
“…Patients with psychiatric illness often present with other medical conditions; the need for an integrated care approach that promotes collaboration among psychiatrists, PCPs, and other medical professionals caring for these patients is well recognized. 29,30 One strategy that has been proven effective in a number of randomized controlled trials is a collaborative care plan that implements active follow-up by a non-physician care manager or nurse, who proactively monitors patients' progress and facilitates care coordination with their physicians. [30][31][32] While the initial costs of setting up such an intervention may be high, in the long term, they are offset by the reduced need for medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since premorbid depression appears to convey considerable risk for substantial symptoms of depression in the aftermath of severe sepsis, hospital programs that target older patients surviving severe sepsis with a prior history of depression—whether or not formally diagnosed—for careful monitoring of their subsequent mental health may improve outcomes. Studies of interventions that combine screening and treatment for comorbid depression and medical conditions in older adults have demonstrated reductions in depressive symptoms, 62 as well as improved physical functioning and medical outcomes. 62,63 …”
Section: Discussionmentioning
confidence: 99%
“…Studies of interventions that combine screening and treatment for comorbid depression and medical conditions in older adults have demonstrated reductions in depressive symptoms, 62 as well as improved physical functioning and medical outcomes. 62,63 …”
Section: Discussionmentioning
confidence: 99%